Differences in Compressive Strength of Hybrid Composites and NanoHybrid Post-Curing Composites Using Dry Heat - Hartanto Endro (Sean Institute, 2025)
Posterior restoration that using composite with indirect tehnique has been widely used by dentist. The variations of the composite fillers has given differ compressive strenght, flexibility, and durability. The aim of this research is to study the compressive strength between hybrid composite and nanohybrid composite using the dry heat post curing. The research represent a apparent experimental, with samples divided into two groups of each 20 specimens of nanohybrid composite and hybrid composite. All of specimens are polmerised by LED (Light Emitting Diode) curing light for 20 seconds, and post polimerisation with dry sterilisator for 10 minutes at 1100C, excepted a control group. A test was then performed by LRX Plus Llod Instrument at 1 mm/minute speed. The result is showed that compressive strength of nanohybrid composite value 192,52 mpa more than hybrid composite which value 156,65 mpa. Analyse t-test statistic presented unsignificant result. It was summarized that there are no significat different between nanohybrid composite and hybrid composite post cured with dry sterilisation.